Prediction of genetic gains with selection between and within S2 progenies of papaya using the REML/Blup analysis - Silva, Tamiris Pereira da; Vidal Neto, Frascisco das Chagas; Silva, Júlio César DoVale (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to predict the genetic gains with selection of superior individuals within papaya (Carica papaya) progenies using the REML/Blup analysis. Thirty-six S2 progenies, originated from the Calimosa and Tainung 1 hybrids, and two commercial control checks were evaluated in a randomized complete block design, with four replicates. The following traits were evaluated: heights of plants and first fruit; stem diameter at 12 and 18 months; number of days required for fruiting; number, mass, and average mass of commercial fruit; and number and mass of carpelloid and pentandric fruit. The magnitudes of the genetic parameters indicated that the variability present in most of the characters allows greater genetic gain if the selection is made at the progeny level, and not in individual plants. For selection among progenies, PROT-268, PROT-74, PROT-55, and PROT-22 were the most promising, with the greatest genetic gain for the studied characters. In the selection among and within progenies, the prediction of the gains is higher for the increase in the expression of the number of commercial fruit and for the decrease in the expression of pentandric fruit.